Content validity, interpretability, and internal consistency of the “Quality First” assessment to evaluate movement quality in hop tests following ACL rehabilitation. A cross-sectional study - Mathieu-Kälin, Moritz; Müller, Mirjam; Weber, Melanie; Caminada, Sandro; Häberli, Marina; Baur, Heiner (Frontiers in Sports and Active Living, 2023)
Introduction: Current approaches fail to adequately identify sport readiness after anterior cruciate ligament (ACL) rehabilitation. Altered landing biomechanics after ACL reconstruction are associated with increased risk of a non-contact ACL re-injury. There is a lack of objective factors to screen for deficient movement patterns. Therefore, the aim of this study was to investigate content validity, interpretability, and internal consistency for the newly developed “Quality First” assessment to evaluate movement quality during hop tests in patients after ACL rehabilitation. Method: Participants in this cross-sectional study were recruited in collaboration with the Altius Swiss Sportmed Center in Rheinfelden, Switzerland. After a successful ACL reconstruction, the movement quality of 50 hop test batteries was evaluated between 6 and 24 months postoperatively with the “Quality First” assessment. Content validity was assessed from the perspective of professionals. To check the interpretability, classical test theory was employed. The Cronbach’s α was calculated to evaluate internal consistency. Results: Content validity resulted in the inclusion of three different hop tests (single leg hop for distance (SLHD), vertical hop (VH), side hop (SH)). The “Quality First” assessment is enabled to evaluate movement quality in the sagittal, vertical and the transversal plane. After the exclusion process, the “Quality First” assessment was free from floor and ceiling effects and obtained a sufficient Cronbach’s α. The final version consists of 15 items, rated on a 4-point scale. Discussion: By means of further validations, the “Quality First” assessment could offer a possibility to evaluate movement quality after ACL rehabilitation during hop tests.